Molecular Response in Patients with Chronic Myeloid Leukemia Treated with Imatinib - Single Centre Experience - Pavkovic M; Angelkovic R; Popova-Simjanovska M; Genadieva-Stavric S; Cevreska L; Stojanovic A (Македонска академија на науките и уметностите. Одделение за медицински науки = Macedonian Academy of Sciences and Arts. Section of Medical Sciences/SCIENDO, 2015)
Introduction of tyrosine kinase inhibitors (TKI) dramatically improves the treatment and survival of the patients with chronic myeloid leukemia (CML) in the last decade. Imatinib (IM) and other TKI induce larger percentage of complete cytogenetic response (CCyR) and major molecular response (MMR). Treatment resistance to TKIs still remains an important problem in the treatment of CML. The aim of our study was to analyze the molecular response (MR) in CML patients treated with Imatinib in our institution. We have analyzed 53 CML patients (pts), 28 females and 25 males, treated with IM as a front or second line treatment. Only 15 pts were treated with IM as a front-line therapy, while 38 pts were pretreated with hydroxyurea or/and interferon. Median duration of CML was 6 years (range: 1 year- 17 years). Median duration of IM treatment was 3 years (range: 1 year-10 years). MR was analyzed in one up to 8 time points with Real Time Quantitative RT-PCR method. Forty six pts (87%) had complete hematological response and 55% of pts had MMR, 13/53(24.5%) pts had MMR at 4.0-4.5 log and 16/53(30.2%) pts had MMR at 3.0-4.0 log. MMR was not achieved in 24/53(45.3%). Our results have shown smaller percentage of patients (55%) with MMR, mostly due to the fact that larger proportion of patients (38/53) were heavily pretreated with HU or/and Interferon for a prolonged period of time, before the IM treatment. This is a major risk factor for acquisition of additional molecular and cytogenetic abnormalities responsible for IM resistance and poor treatment response.